Effect of bile on Vibrio parahaemolyticus. - Pace, J L (1997)
Many enteric pathogens are thought to enter a viable but nonculturable state when deprived of nutrients. Virulent strains of the enteric pathogen Vibrio parahaemolyticus are rarely isolated from their low-nutrient aquatic environments, possibly due to their nonculturability. Host factors such as bile may trigger release from dormancy and increase virulence in these strains. In this study, the addition of bile or the bile acid deoxycholic acid to estuarine water-cultured bacteria led to an increase in the direct viable count and colony counts among the virulent strains. This effect was not demonstrated in the nonvirulent strains, and it was reversed by extraction of bile acids with cholestyramine. Bile-treated V. parahaemolyticus had lower levels of intracellular calcium than untreated cells, and this effect coincided with an increase in the number of metabolically active cells. Chelation of intracellular calcium with BAPTA/AM (R. Y. Tsien, Biochemistry 19:2396-2402, 1980) produced similar results. Addition of bile to V. parahaemolyticus cultures in laboratory medium enhanced factors associated with virulence such as Congo red binding, bacterial capsule size, and adherence to epithelial cells. These results suggest that a bile acid-containing environment such as that found in the human host favors growth of virulent strains of V. parahaemolyticus and that bile acids enhance the expression of virulence factors. These effects seem to be mediated by a decrease in intracellular calcium.